PRIMER REGISTRO DE UN PULPO DE LA FAMILIA TREMOCTOPODIDAE (CEPHALOPODA: OCTOPODA) PARA EL CARIBE COLOMBIANO (Boletín de Investigaciones Marinas y Costeras, 2016)
The Tremoctopodidae is a small group of epipelagic to mesopelagic octopuses with a single genus (Tremoctopus) and three recognized species. Of them, T. violaceus is known to occur in Atlantic waters between 40°N and 35°S, including the Mediterranean and the Gulf of Mexico, with only two records for the Caribbean (Cayman Islands and eastern Venezuela). An adult female of this species was recently collected at Islas del Rosario, off Cartagena, Colombia, constituting the first record of this species for Colombia.